PERANAN KEPALA ORGANISASI PERANGKAT DAERAH (OPD) DALAM MENGAKTUALISASIKAN CORE VALUES BerAKHLAK (BERORIENTASI PELAYANAN) PADA APARATUR SIPIL NEGARA (ASN) - Muhammad Noer, MBS (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This study aims to analyze the implementation of BerAKHLAK socialization, the role of leadership in actualizing BerAKHLAK core values, and analyzing the role of leadership in public services in the Riau Provincial Government. This study uses a qualitative method approach by distributing questionnaires to related officials, as many as 61 respondents using a purposive sampling approach, Data collection techniques using questionnaires with a scale of 1-5, which then uses qualitative descriptive analysis. The findings in this study are that the implementation of BerAKHLAK core values ​​​​socialization has been carried out from 2022 to 2025, the role of the Head of OPD in actualizing BerAKHLAK core values ​​​​is very large, and his role is more operational, strategic, and managerial in public services namely as a strategic planner, driver of innovation in services, quality assurance, as a developer of ASN competencies and as a supervisor of the course of service as internal supervision.